1986
DOI: 10.1126/science.2425434
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Sodium Channels in Spontaneously Contracting Vascular Muscle Cells

Abstract: Electrophysiological recordings of inward currents from whole cells showed that vascular muscle cells have one type of sodium channel and two types of calcium channels. One of the calcium channels, the transient calcium channel, was activated by small depolarizations but then rapidly inactivated. It was equally permeable to calcium and barium and was blocked by cadmium, but not by tetrodotoxin. The other type, the sustained calcium channel, was activated by larger depolarizations, but inactivated very little; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 25 publications
7
73
1
Order By: Relevance
“…Recently, an l.v.a. Ca2+ current sensitive to holding potential, carried by Ca2+ and Ba2+ ions, has also been reported in heart cells (Bean, 1985;Nilius, Hess, Lansman & Tsien, 1985;Mitra & Morad, 1986), twitch muscle fibres (Cota & Stefani, 1986), rat myoballs (Cognard, Lazdunski & Romey, 1986) and in vascular smooth muscle cells (Sturek & Hermsmeyer, 1986). …”
Section: Separation Of Lva Currentsmentioning
confidence: 99%
“…Recently, an l.v.a. Ca2+ current sensitive to holding potential, carried by Ca2+ and Ba2+ ions, has also been reported in heart cells (Bean, 1985;Nilius, Hess, Lansman & Tsien, 1985;Mitra & Morad, 1986), twitch muscle fibres (Cota & Stefani, 1986), rat myoballs (Cognard, Lazdunski & Romey, 1986) and in vascular smooth muscle cells (Sturek & Hermsmeyer, 1986). …”
Section: Separation Of Lva Currentsmentioning
confidence: 99%
“…In the vascular muscles (rat mesentric artery [1]; rat portal verb [36]; dog saphenous vein [66]; cell line (A 10) from embryonic rat aorta [24]; primary culture of rat azygos vein [54]), evidence is presented for the existence of two different types of Ca channel. One type is activated by small depolarization ("low threshold") and inactivated relatively quickly ("fast" channels), and the other is activated by large depolarization ("high threshold") and inactivated relatively slowly ("slow" channels).…”
Section: Voltage-operated Ca Channelsmentioning
confidence: 99%
“…Na channel No clear evidence has been presented so far for the existence of Na channel in smooth muscles under the physiological condition, except for primary cultures of azygos venous muscle cells from neonatal rats [54]. In this cell, the inward current carried by Na was recorded under whole-cell clamp.…”
Section: Other Ionic Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that, in vascular smooth muscle, action potentials are not dependent on Na + channels since tetrodotoxin (TTX) has no effect on amplitude and duration of action potentials [18], leading to the belief that these channels might not be present or prominent in these tissues. Nonetheless, Na + currents (I Na ) have been measured in visceral smooth muscles such as myometrium and uterus (pregnant), colon, esophagus, stomach, and ureter as well as in certain vascular smooth muscles such as the portal and azygos veins [2,8,[24][25][26]31,33,34]. The identification of functional voltage-gated Na + channels in quiescent and proliferating vascular smooth muscle cells (VSMC), however, has not been as forthcoming.…”
Section: Introductionmentioning
confidence: 99%